The Effect of the Dapic Problem-Solving Process Learning Model on Students' Critical Thinking Skills in Colloid System Material - Lidia Aulia Nisa; Tonih Feronika; Aini Nadhokhotani Herpi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to examine the effect of the DAPIC Problem-Solving Process learning model on students' critical thinking skills in colloid system material. The DAPIC model consists of five stages: Define, Assess, Plan, Implement, and Communicate, designed to help students develop critical thinking skills through a structured learning process relevant to everyday life. The research employs a quantitative approach, measuring critical thinking skills based on indicators developed by Ennis (1995). The method used is a quasi-experimental design with a nonequivalent control group design. The sampling technique is purposive sampling, with 32 students in each group: class XI-2 as the experimental group and class XI-1 as the control group. The research instrument is an essay test adapted to Ennis's critical thinking indicators. The results show that the significance value (Sig.) is 0.000 < α (0.05), leading to the rejection of H0 and acceptance of H1. This indicates that the DAPIC Problem-Solving Process learning model significantly affects students' critical thinking skills in colloid system material.